Human vs. Transhuman: Act One - Cecilia Suhr (Journal of the Association for Technology in Music Instruction, 2025)
This work investigates the conflict between human and transhuman; to that end, the performance employs visual representations of human and transhuman interaction. The music and visual realms interact in real time to enhance the immersive experience of understanding the tension between machines and humans. Voice improvisation also interacts with live processing to create a unique sonic landscape. Overall, this is a multimedia, experimental contemporary performance at the intersection of technology and acoustic music.
Keywords: composition